Into the storm - Avi (New York : Scholastic, 1996)
Avi's suspenseful seafaring adventure ESCAPE FROM HOME continues in INTO THE STORM.Fifteen-year-old Maura and twelve-year-old Patrick O'Connell are finally free from the impoverished conditions of their small Irish village. Though they've made it onto the ship to America, there's still a treacherous journey ahead of them.In the storage hold, ten-year-old Laurence Kirkle struggles to survive and stay hidden as the ship's crew searches for stowaways to throw overboard. All three children are in search of a better world and a new home. But will they find what they're looking for in America?Once again, Avi skillfully creates an edge-of-your-seat adventure brimming with action and heart.
Keywords: Storms; Ocean; Ships